What she said the art of inspiring action through speech - Lunin, Monica (Milton, Qld John Wiley and Sons Australia, Ltd, 2022)
Learn how spoken words can change a mind, a community and the world with this collection of remarkable speeches by women. What She Said is an inspiring collection of speeches from passionate and persuasive women from around the world and throughout history. The included speakers come from diverse cultural and ethnic backgrounds, ages, and education levels, demonstrating how women from all walks of life can use the power of speech to bring change. Author Monica Lunin has curated and analysed 40 of the greatest speeches made by strong and empowering women from all around the world. From Queen Elizabeth I to Maya Angelou, Greta Thunberg, Julia Gillard, and Michelle Obama, What She Said shows not only what was said but also how the speech worked and why it was effective. In this insightful exploration of female wit, persuasion, and leadership, you'll find an extract of the speech, a biography of the speaker and a breakdown of the qualities that made it so remarkable. --Provided by publisher.
This collection analyses inspirational speeches from persuasive women from many different walks of life throughout history. From Queen Elizabeth I to Julia Gillard, Maya Angelou to Greta Thunburg, it champions women as great communicators who can teach us how to craft a strong message. This book will help readers build their speaking skills by showing how women of all ages, from extremely diverse backgrounds, have used the power of speech and their unique voices to make a difference in the world.
Introduction -- 1. Providing guidance, advice and wisdom -- Michelle Obama: When they go low, we go high -- Nora Ephron: Be the heroine of your life -- Florence Nightingale: What makes a good nurse -- Virginia Woolf: Shakespeare's sister -- 2. Sharing complex thoughts and ideas -- Brene Brown: The power of vulnerability -- Hannah Arendt: What remains? The language remains -- Marie Curie: Radium and the new concepts in chemistry -- Margaret Atwood: Payback: Debt and the shadow side of wealth -- 3. Opening hearts and minds -- Eleanor Roosevelt: On the adoption of the Universal Declaration of Human Rights -- Nancy Astor: Maiden speech -- Malala Yousafzai: One girl among many -- Naomi Klein: This changes everything -- 4. Beckoning the waves of feminism -- Mary Wollstonecraft: I have a dream -- Emmeline Pankhurst: Why we are militant -- Betty Friedan: Call to women's strike for equality -- Audre Lorde: The Transformation of Silence -- 5. Demanding respect -- Julia Gillard: Misogyny speech -- Sylvia Rivera: Y'all better quiet down -- Margaret Thatcher: The lady's not for turning -- Hillary Clinton: Women's rights are human rights -- 6. Arguing a position -- Ruth Bader Ginsburg: Argument in Frontiero v. Richardson -- Barbara Jordan: Articles of Impeachment during Watergate -- Margaret Sanger: The morality of birth control -- Angela Merkel: Speech to US Congress -- 7. Inspiring action -- Queen Elizabeth I: The heart and stomach of a king -- Sojourner Truth: Ain't I a woman? -- Dolores Ibarruri: They shall not pass! -- Greta Thunberg: Our house is on fire -- 8. Using humour to connect and persuade -- Nellie McClung: Should men vote? -- Dorothy Parker: Hollywood, the land I won't return to -- Roxane Gay: Confessions of a bad feminist -- Ruby Wax: What's so funny about mental illness? -- 9. Encouraging inclusion -- Jacinda Ardern: They were New Zealanders, They are us -- Faith Bandler: Faith, hope and reconciliation -- Indira Gandhi: Last speech of Indira Gandhi at Bhubaneswar -- Linda Burney: Inaugural speech -- 10. Harnessing the power of stories -- Eva Kor: Surviving the Angel of Death -- Josephine Baker: March on Washington -- Svetlana Alexievich: On the battle lost -- Maya Angelou: On the pulse of morning.
Includes bibliographical references and index.
Keywords: Speeches, addresses, etc. -- Women authors; Women -- Communication .; Inspiration